Hydrodesulfurization catalyst as well as preparation method and application thereof
By using composite modified molecular sieve and inorganic heat-resistant matrix in hydrodesulfurization catalysts, combining active metal components, the low direct desulfurization activity and high hydrogen of existing catalysts when treating alkyl-substituted dibenzothiophene compounds is solved. The consumption problem has achieved efficient ultra-deep desulfurization reaction of diesel.
Patent Information
- Application Number
- CN202310712009.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-15
- Publication Date
- 2024-12-20
AI Technical Summary
When the existing hydrodesulfurization catalysts treat alkyl-substituted dibenzothiophene compounds, the direct desulfurization activity and selectivity are low, and the reaction hydrogen consumption is high, making it difficult to achieve ultra-deep desulfurization of diesel.
Using composite modified molecular sieve as a carrier, a rich mesoporous structure and high acid amount are generated by alkali and metal composite modification treatment. Combined with inorganic heat-resistant matrix and active metal components, an additive with high direct desulfurization activity and selectivity is prepared. Hydrogen desulfurization catalyst.
The direct desulfurization path selectivity of the catalyst and the reaction hydrogen utilization efficiency are significantly improved, hydrogen consumption is reduced, and the efficiency of diesel ultra-deep desulfurization reaction is improved.
Smart Images

Figure BDA0004288226970000231 
Figure BDA0004288226970000241 
Figure BDA0004288226970000242
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrodesulfurization, and in particular to a hydrodesulfurization catalyst and a preparation method and application thereof. Background Art
[0002] As various environmental regulations have become increasingly stringent on air pollutant emissions in recent years, countries around the world have formulated more stringent fuel standards. At the same time, oil resources tend to be heavier and inferior, so significantly reducing the content of impurities in fuel and improving the quality of gasoline and diesel products have become urgent issues for major oil refining companies. Among them, the sulfur in diesel has a great impact on motor vehicle exhaust emissions, so the sulfur content in diesel products needs to be strictly limited. Hydrogenation technology is one of the main technologies for producing ultra-low sulfur diesel, which has the characteristics of high desulfurization efficiency, low operating costs, and a wide range of applications. The core of the technology is the hydrogenation catalyst.
[0003] Hydrogenation catalysts are generally made of alumina-supported molybdenum and / or tungsten transition metal sulfide catalysts with cobalt and / or nickel as promoters. The catalysts have a high removal efficiency for sulfur-containing compounds such as benzothiophenes and dibenzothiophenes during the deep hydrodesulfurization of diesel. However, for dibenzothiophene compounds substituted with alkyl groups, especially dibenzothiophene compounds with alkyl substituents at the 4th and 6th positions (such as 4,6-dimethyldibenzothiophene), the steric hindrance effect brought by the alkyl substitution significantly reduces the reactivity of the sulfide, making it difficult to achieve ultra-deep desulfurization of diesel.
[0004] Dibenzothiophene compounds are desulfurized mainly through two reaction pathways. One is the hydrogenation pathway, that is, the sulfide reacts with the catalyst through π-type adsorption, one of the aromatic rings is first hydrogenated and saturated, and then the C-S bond is broken under the action of hydrogen to desulfurize; the other is the direct desulfurization pathway, that is, the sulfide reacts with the catalyst through σ-type adsorption, and the C-S bond of the thiophene ring is directly broken to remove sulfur. However, for dibenzothiophene compounds with alkyl substitution, the steric hindrance effect brought by the alkyl substitution significantly inhibits the σ-type adsorption of the sulfide, while the effect on the π-type adsorption is small, resulting in a significant decrease in the direct desulfurization activity of the catalyst and a decrease in the overall hydrogenation desulfurization activity.
[0005] At present, industrial ultra-deep desulfurization catalysts basically achieve the conversion of 4,6-dimethyldibenzothiophene (4,6-DMDBT) through a hydrogenation pathway that first hydrogenates and saturates the aromatic ring and then desulfurizes it, but this pathway consumes a lot of hydrogen. In order to improve the desulfurization rate of the catalyst and reduce hydrogen consumption at the same time, researchers have proposed a variety of new catalyst preparation and modification methods.
[0006] Patent application CN1184843A discloses a diesel hydroconversion catalyst, wherein the catalyst carrier is obtained by mixing, molding and calcining 40-80 wt% alumina, 0-20 wt% amorphous silicon aluminum and 5-30 wt% Y-type molecular sieve, wherein the Y-type molecular sieve used has a pore volume of 0.4-0.52 mL / g and a specific surface area of 750-900 m 2 / g, SiO2 / Al2O3 ratio is 7-15, and the active metal components are nickel and tungsten. The catalyst has high hydrodesulfurization activity, but the yield of diesel is reduced and the cetane number changes slightly.
[0007] Patent application CN105772109A discloses a hydrodesulfurization catalyst, wherein the carrier of the catalyst is obtained by mixing, molding and calcining 50-98 wt% of alumina and 1-30 wt% of zirconium-modified high silicon-aluminum ratio Y-type molecular sieve, wherein the content of zirconium oxide is 0.1-6 wt% of the mass of the zirconium-modified Y-type molecular sieve. The hydrodesulfurization catalyst prepared by the carrier has high desulfurization activity and high diesel yield, but the catalyst mainly removes difficult-to-desulfurize compounds through hydrogenation, and the hydrogen consumption in the reaction process is high.
[0008] Patent application CN106391097A discloses the synthesis of a porous ZSM-5 zeolite and γ-Al2O3 composite material and the preparation of a hydrodesulfurization catalyst. The synthesized composite material has a multi-level pore structure, good hydrothermal stability and high mechanical strength. The addition of ZSM-5 zeolite makes the composite material carrier and the loaded metal species have a weaker interaction, which is beneficial to the reduction and sulfidation of the metal species, and is easy to form a highly active multi-layer molybdenum sulfide or tungsten sulfide active phase on the composite material, thereby improving the hydrodesulfurization performance of the metal sulfide catalyst and the conversion rate of 4,6-DMDBT. However, since ZSM-5 zeolite is a ten-membered ring pore, it is difficult for 4,6-DMDBT with a larger molecular size to enter its pores, reducing the utilization rate of the acid centers on the rich inner surface of ZSM-5 zeolite.
[0009] Patent application CN103787368A discloses a mesoporous ZSM-5 zeolite-supported metal sulfide catalyst and its application. The mesoporous ZSM-5 zeolite is synthesized using tetrapropylammonium hydroxide as a structure directing agent and a high molecular polymer containing a quaternary amine group as a template agent, and nickel and molybdenum are used as active metal components to prepare the catalyst. The catalyst is used in the hydrodesulfurization of 4,6-DMDBT and the hydrocracking reaction of n-decane, which can greatly improve the raw material conversion rate, but the product distribution is not given.
[0010] IM-5 molecular sieve belongs to IMF structure molecular sieve, with a two-dimensional ten-membered ring pore structure, and a large limited pore in the third dimension. Its pore structure is similar to that of ZSM-5 molecular sieve. At the same time, the molecular sieve also has a twelve-membered ring cage structure, which can provide more reaction and diffusion space for reactants. Patent application CN106391100A discloses a modified IM-5 molecular sieve and its preparation method and application. By modifying the molecular sieve with an alkaline solution containing quaternary ammonium cations and quaternary phosphonium cations, the molecular sieve can have more mesopores, while maintaining good thermal stability and hydrothermal stability, and improving the performance of catalyzing the alkylation reaction of toluene and methanol.
[0011] The hydrodesulfurization catalysts provided by the prior art can meet the requirements of some ultra-deep desulfurization reactions. However, since the direct desulfurization selectivity of the catalyst is not high, the removal of difficult-to-desulfurize compounds is mainly achieved through the hydrogenation pathway, and the hydrogen consumption in the reaction process is relatively high. Summary of the invention
[0012] The purpose of the present invention is to overcome the problem that the hydrodesulfurization catalyst in the prior art cannot have good direct desulfurization activity, direct desulfurization path selectivity and reaction hydrogen consumption, and to provide a hydrodesulfurization catalyst and a preparation method and application thereof. In the hydrodesulfurization catalyst, a composite modified molecular sieve is selected as a part of the carrier. The composite modified molecular sieve has a rich mesoporous structure and a high acid content. When used as a hydrodesulfurization catalyst carrier, the hydrodesulfurization catalyst has good desulfurization activity and direct desulfurization selectivity, and has low reaction hydrogen consumption.
[0013] In order to achieve the above-mentioned object, the first aspect of the present invention provides a hydrodesulfurization catalyst, wherein the catalyst comprises a carrier, an active component supported on the carrier and an optional auxiliary agent, wherein the carrier comprises an inorganic heat-resistant matrix and a composite modified molecular sieve, wherein the composite modified molecular sieve comprises a molecular sieve and a modifying component, wherein the modifying component is selected from at least one of the metals of Group VIB; based on the total amount of the composite modified molecular sieve, the content of the modifying component in terms of oxide is 1-20 wt %; based on the total amount of the composite modified molecular sieve, the total acid content of the composite modified molecular sieve is 0.85-1.5 mmol NH3·g -1 The proportion of the mesopore volume of the composite modified molecular sieve to the total pore volume is 20-80%; the active component includes at least one of the metals of Group VIII and at least one of the metals of Group VIB, and the auxiliary agent is selected from at least one of fluorine, phosphorus and boron.
[0014] Preferably, the preparation method of the composite modified molecule comprises: contacting the molecular sieve with a base for at least one base modification, performing a first drying and a first calcination in sequence after ammonium exchange, and then introducing the modified component into the molecular sieve for metal modification.
[0015] A second aspect of the present invention provides a method for preparing a hydrodesulfurization catalyst, wherein the method comprises:
[0016] (1) mixing an inorganic heat-resistant matrix and / or its precursor with a composite modified molecular sieve to form a mixture, and then performing a third drying and a third calcination to obtain a carrier;
[0017] (2) impregnating the support of step (1) with a solution containing an active component and an optional promoter precursor, and then performing a fourth drying and a fourth calcination to obtain a hydrodesulfurization catalyst;
[0018] The active component is selected from at least one of the metal elements of Group VIII and at least one of the metal elements of Group VIB; the auxiliary agent is selected from at least one of fluorine, phosphorus and boron;
[0019] Based on the total amount of the composite modified molecular sieve, the content of the modified component calculated as oxide is 1-20 wt %; based on the total amount of the composite modified molecular sieve, the total acid content of the composite modified molecular sieve is 0.85-1.5 mmol NH3·g -1 The mesoporous volume of the composite modified molecular sieve accounts for 20-80% of the total pore volume.
[0020] The third aspect of the present invention provides a use of the hydrodesulfurization catalyst described in the first aspect or the hydrodesulfurization catalyst prepared by the preparation method described in the second aspect in the hydrodesulfurization reaction of a raw material containing sterically hindered molecules.
[0021] The inventors of the present invention have found in their research that the composite modified molecular sieve provided by the present invention has a rich mesoporous structure and a high acid content. When the composite modified molecular sieve is used as a carrier component in a hydrodesulfurization catalyst, it is beneficial for the reactant molecules to contact more acid centers on the surface of the molecular sieve, promoting the conversion of the reactant molecules, and some active components can be pre-dispersed on the defective sites of the molecular sieve after modification, which is beneficial to enhance the interaction between the active metal and the molecular sieve, so that the active components and the acid centers play a synergistic effect and promote the hydrodesulfurization reaction. Furthermore, the composite modified molecular sieve and the inorganic heat-resistant matrix are combined to form a catalyst. As a carrier, the active component and the optional auxiliary agent are then loaded to prepare a hydrodesulfurization catalyst. The hydrodesulfurization catalyst has both enhanced direct desulfurization activity and direct desulfurization path selectivity, and the hydrogen consumption in the reaction process is reduced, so that it has good application prospects in the ultra-deep desulfurization reaction of diesel. For example, the direct desulfurization path selectivity of the catalyst in Example 7 is 22.8%, and the direct desulfurization relative activity is 182, which are much higher than the direct desulfurization path selectivity and direct desulfurization relative activity in Comparative Examples 5-8; and the reaction hydrogen consumption of Example 7 is 4.59%, which is much lower than the reaction hydrogen consumption of Comparative Examples 5-8.
[0022] Preferably, in the process of preparing the composite modified molecular sieve of the present invention, the molecular sieve is subjected to composite modification with alkali and metal, which can produce more mesoporous structures and increase the acid content of the composite modified molecular sieve. DETAILED DESCRIPTION
[0023] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0024] The first aspect of the present invention provides a hydrodesulfurization catalyst, wherein the catalyst comprises a carrier, an active component supported on the carrier, and an optional auxiliary agent, wherein the carrier comprises an inorganic heat-resistant matrix and a composite modified molecular sieve, wherein the composite modified molecular sieve comprises a molecular sieve and a modified component, wherein the modified component is selected from at least one of the metals of Group VIB; based on the total amount of the composite modified molecular sieve, the content of the modified component in terms of oxide is 1-20 wt %; based on the total amount of the composite modified molecular sieve, the total acid content of the composite modified molecular sieve is 0.85-1.5 mmol NH3·g -1 The proportion of the mesopore volume of the composite modified molecular sieve to the total pore volume is 20-80%; the active component includes at least one of the metals of Group VIII and at least one of the metals of Group VIB, and the auxiliary agent is selected from at least one of fluorine, phosphorus and boron.
[0025] In the present invention, the total acid content of the composite modified molecular sieve is determined by the NH3-TPD method, see "Research Methods of Solid Catalysts, Petrochemicals, 30(12), 2001: 952".
[0026] The catalyst provided by the present invention combines a composite modified molecular sieve and an inorganic heat-resistant matrix as a carrier, and then loads an active component and an optional auxiliary agent to prepare a hydrodesulfurization catalyst. The hydrodesulfurization catalyst has high direct desulfurization activity, significantly improved selectivity in the direct desulfurization path, and reduced hydrogen consumption in the reaction process, so that it has good application prospects in the ultra-deep desulfurization reaction of diesel.
[0027] In the present invention, there is no specific restriction on the content of each substance in the catalyst. Preferably, based on the total amount of catalyst, the content of the inorganic heat-resistant matrix is 20-80% by weight, the content of the composite modified molecular sieve is 5-40% by weight, the content of the Group VIII metal calculated as oxide is 2-10% by weight, the content of the Group VIB metal calculated as oxide is 10-40% by weight, and the content of the auxiliary agent calculated as oxide is 0-8% by weight; further preferably, based on the total amount of catalyst, the content of the inorganic heat-resistant matrix is 30-70% by weight, the content of the composite modified molecular sieve is 5-30% by weight, the content of the Group VIII metal calculated as oxide is 2-8% by weight, the content of the Group VIB metal calculated as oxide is 10-30% by weight, and the content of the auxiliary agent calculated as oxide is 0-7% by weight. It should be noted that the content of the VIB group metal here does not include the content of the VIB group metal element in the composite modified molecular sieve; it should be further noted that when the VIII group metal is Co, the Co content in the catalyst is calculated as CoO, when the VIB group metal is Mo, the Mo content in the catalyst is calculated as MoO3, and when the additive is phosphorus, the P content in the catalyst is calculated as P2O5. This preferred embodiment is used to balance and regulate the activity of each reaction path of the hydrodesulfurization of the catalyst, improve the selectivity and activity of the desulfurization reaction, and reduce the occurrence of side reactions.
[0028] In the present invention, the content of each component is calculated by the feed amount.
[0029] In the present invention, the inorganic heat-resistant matrix conventionally defined in the art is applicable to the present invention, and those skilled in the art can select it according to specific needs. Preferably, the inorganic heat-resistant matrix is selected from at least one of aluminum oxide, silicon oxide, titanium oxide, magnesium oxide, aluminum oxide-magnesium oxide, silicon oxide-aluminum oxide, silicon oxide-magnesium oxide, silicon oxide-zirconium oxide, silicon oxide-thorium oxide, silicon oxide-beryllium oxide, silicon oxide-titanium oxide, silicon oxide-aluminum oxide-thorium oxide, silicon oxide-aluminum oxide-titanium oxide, silicon oxide-aluminum oxide-magnesium oxide, silicon oxide-aluminum oxide-zirconium oxide, phosphorus oxide-aluminum oxide, phosphorus oxide-silicon oxide-aluminum oxide, and natural zeolite, preferably aluminum oxide.
[0030] In a preferred embodiment, the aluminum oxide is selected from at least one of aluminum oxide, aluminum hydroxide, hydrated aluminum oxide and amorphous aluminum hydroxide having X-ray diffraction characteristics of γ, η, θ, δ and χ. Aluminum oxide can be purchased commercially or prepared by existing methods.
[0031] The use of the above preferred alumina can provide the catalyst with a large specific surface area and pore volume, promote the dispersion of active metals on the alumina, and improve the activity and stability of the catalyst.
[0032] In the present invention, the active component has a wide range of selection. Preferably, the active component is selected from at least one of iron, cobalt, nickel, ruthenium, rhodium, palladium, osmium, iridium and platinum and at least one of chromium, molybdenum and tungsten, and more preferably molybdenum and / or tungsten and cobalt and / or nickel.
[0033] In the present invention, the molecular sieve is modified by introducing a modifying component and regulating the content of the modifying component. Preferably, based on the total amount of the composite modified molecular sieve, the content of the modifying component calculated as oxide is 1-10% by weight, for example, 1% by weight, 2% by weight, 3% by weight, 4% by weight, 5% by weight, 6% by weight, 7% by weight, 8% by weight, 9% by weight, 10% by weight, and values between any two groups of data.
[0034] The composite modified molecular sieve provided by the present invention can provide more acid sites and has a higher acid content. Preferably, based on the total amount of the composite modified molecular sieve, the total acid content of the composite modified molecular sieve is 0.85-1 mmol NH3·g -1 , for example, 0.85 mmol NH3·g -1 、0.86mmol NH3·g -1 、0.87mmol NH3·g -1 、0.88mmol NH3·g -1 、0.89mmol NH3·g -1 、0.9mmol NH3·g -1 、0.91mmol NH3·g -1 、0.92mmol NH3·g -1 、0.93mmolNH3·g -1 、0.94mmol NH3·g -1 、0.95mmol NH3·g -1 、0.96mmol NH3·g -1 、0.97mmol NH3·g -1 、0.98mmol NH3·g -1 、0.99mmol NH3·g -1 、1mmol NH3·g -1 And the values between any two sets of data. The use of this preferred embodiment is conducive to improving the selectivity of the hydrodesulfurization target reaction path.
[0035] The composite modified molecular sieve provided by the present invention has a rich mesoporous structure, which promotes the direct desulfurization reaction and improves the direct desulfurization activity. Preferably, the ratio of the mesoporous volume of the composite modified molecular sieve to the total pore volume is 25-75%, for example, it can be 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% and the value between any two groups of data, and more preferably 50-70%.
[0036] In the present invention, the mesopores of the composite modified molecular sieve refer to the molecular sieve pores with a pore size greater than 2 nm and less than 50 nm, and the pore volume is measured using the GB / T 5816-1995 standard method.
[0037] In the present invention, there is no particular limitation on the type of the modifying component. Preferably, the modifying component is selected from at least one of chromium, molybdenum and tungsten, preferably molybdenum and / or tungsten, and more preferably molybdenum. This preferred embodiment is conducive to pre-dispersing the active metal on the surface of the molecular sieve, promoting the synergistic effect between the acid center and the active metal, and improving the desulfurization activity of the catalyst under the conditions of the hydrodesulfurization reaction.
[0038] In a preferred embodiment, based on the total amount of the composite modified molecular sieve, the content of the molecular sieve is 80-99% by weight, the content of molybdenum oxide is 1-10% by weight, and the content of tungsten oxide is 0-10% by weight; preferably, based on the total amount of the composite modified molecular sieve, the content of the molecular sieve is 82-99% by weight, the content of molybdenum oxide is 1-9% by weight, and the content of tungsten oxide is 0-9% by weight. This preferred embodiment helps to obtain a higher specific surface area, pore volume and total acid content while maintaining the stability of the molecular sieve framework, thereby improving the desulfurization activity of the catalyst.
[0039] In the present invention, there is no particular limitation on the type of molecular sieve. Preferably, the molecular sieve is selected from at least one of an IMF type molecular sieve, an MFI type molecular sieve, a Beta type molecular sieve, a MOR type molecular sieve and a FAU type molecular sieve, and more preferably an IMF type molecular sieve. This preferred embodiment is helpful to obtain a composite modified molecular sieve with high molecular sieve framework stability, rich mesoporous structure and high acid content.
[0040] In the present invention, there is no particular limitation on the specific type of the IMF type molecular sieve, and IM-5 is used as a schematic illustration in the present invention.
[0041] In the present invention, there is no specific limitation on the source of the molecular sieve, and the molecular sieve can be obtained from the market or by self-production. For example, the IMF type molecular sieve in the present invention is prepared by the Petrochemical Science Research Institute with reference to the method in the patent application CN102452666A. Specifically, the IMF type molecular sieve is prepared by the following method:
[0042] (1) dissolving an inorganic base, an aluminum source, and a template agent in water to prepare a mixed solution;
[0043] (2) adding a silicon source to the mixed solution of step (1) and mixing to form a colloid or a solid-liquid mixture;
[0044] (3) transferring the colloid or solid-liquid mixture obtained in step (2) to a crystallization kettle, crystallizing at a temperature of 120-200° C. for 1-10 days, cooling the obtained mixed solution after completion of the crystallization, and subjecting the obtained mixed solution to ammonium exchange, filtration, washing, drying and calcination to obtain the IMF type molecular sieve;
[0045] The silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the molar ratio of the silicon source, the aluminum source, the oxide of the alkali metal, the template and water is 1: 0.005-0.1: 0.1-0.35: 0.01-0.3: 5-30.
[0046] In the present invention, in the method for preparing the IMF type structured molecular sieve, the silicon source is selected from at least one of silica sol, solid silica gel and water glass.
[0047] In the present invention, in the method for preparing the IMF type structured molecular sieve, the aluminum source is selected from at least one of aluminum chloride, aluminum sulfate, aluminum nitrate and sodium metaaluminate.
[0048] In the present invention, in the method for preparing the IMF type structured molecular sieve, the alkali source is sodium hydroxide and / or potassium hydroxide.
[0049] In the present invention, in the method for preparing the IMF type structured molecular sieve, the template agent is a diquaternary ammonium salt, for example, a salt of 1,5-bis(N-methylpyrrolidine)pentane.
[0050] In the present invention, in the preparation method of the IMF type structure molecular sieve, the filtration, washing and drying can be carried out in any manner conventionally known in the art. Specifically, for example, the filtration is a reaction mixture obtained by suction filtration. The washing can be carried out, for example, with deionized water until the pH value of the filtrate reaches 7-9. The drying conditions are: temperature 80-120°C, time 4-15 hours. In the present invention, a calcination step can also be included; the calcination can be carried out in any manner conventionally known in the art, the calcination temperature is 350-750°C, the calcination time is 2-8 hours, and the calcination atmosphere is generally air or oxygen.
[0051] The IMF-type structured molecular sieve obtained by this preparation method has a higher acid content, which is conducive to expanding its application in acid-catalyzed reactions. Applying it to the composite modified molecular sieve of the present invention can further increase the acid content of the composite modified molecular sieve; the molecular sieve has a large specific surface area and pore volume, which is conducive to promoting the reaction of the reaction molecules on the surface of the molecular sieve and the diffusion in the pores.
[0052] In a preferred embodiment, the preparation method of the composite modified molecular sieve includes: the molecular sieve is contacted with a base for at least one base modification, ammonium exchange is followed by a first drying and a first calcination, and then a modifying component is introduced into the molecular sieve for metal modification. The composite modification treatment of the molecular sieve by introducing a base and a modifying component (preferably, the modifying component is a metal element of Group VIB) in this preferred embodiment can produce more mesopores in the molecular sieve, and part of the active metal component is pre-dispersed on the molecular sieve, which is conducive to enhancing the interaction between the active metal and the molecular sieve.
[0053] In the present invention, the types and contents of the molecular sieve and the modified component have been described in the foregoing content and will not be repeated here.
[0054] In the present invention, there is no particular limitation on the type of alkali used in the alkali modification treatment. Preferably, the alkali is selected from at least one of sodium hydroxide, potassium hydroxide, ammonium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate and potassium bicarbonate, preferably sodium hydroxide and / or potassium hydroxide. The use of this preferred embodiment helps to ensure that the molecular sieve skeleton structure is basically stable, not only to produce a certain number of mesopores in the molecular sieve, which is conducive to the contact of the macromolecular reactant with the acid center on the inner surface of the molecular sieve, but also the defect sites generated by the desiliconization of the skeleton are more likely to interact with the active metal of the VIB group, promote the synergistic effect between the acid center and the active metal, and increase the total acid content of the molecular sieve.
[0055] In the present invention, there is no particular limitation on the concentration of the base. Preferably, the concentration of the base is 0.001-0.5 mol / L, preferably 0.05-0.1 mol / L.
[0056] In the present invention, the liquid-to-solid ratio of the mixed solution during alkali modification is 10-40 mL / g, preferably 15-30 mL / g.
[0057] In the present invention, the conditions for alkali modification have a wide range of selection. Preferably, the conditions for alkali modification include: temperature of 60-120°C, time of 0.5-8h; more preferably, the conditions for alkali modification include: temperature of 60-100°C, time of 0.5-6h.
[0058] In a preferred embodiment, the number of base modification is 1-3 times, preferably 1-2 times. With this preferred embodiment, abundant mesopores can be obtained, while ensuring that the molecular sieve has high structural stability and high acid content.
[0059] In the present invention, base modification helps to increase the specific surface area and pore volume of the molecular sieve and increase the total acid content while maintaining the stability of the molecular sieve framework.
[0060] According to a preferred embodiment of the present invention, the alkali treatment includes: mixing the molecular sieve with water (preferably deionized water) to make a mixed molecular sieve slurry, then dissolving the alkali in water (preferably deionized water) to prepare an alkali solution, and then dividing the alkali solution into 2-8 equal volumes, adding 1 portion to the molecular sieve slurry every 0.08-0.5h, and continuing to stir evenly for 0.17-4h after the addition of the alkali solution is completed, and then washing, filtering, ammonium exchange, first drying and first roasting to obtain an alkali-modified molecular sieve. In the present invention, it can be understood that the alkali described in the foregoing content is provided by an alkali solution, and the concentration of the alkali is the concentration of the alkali solution.
[0061] In the present invention, there is no particular limitation on the conditions for ammonium exchange. Preferably, the conditions for ammonium exchange include: a temperature of 60-100° C. and a time of 0.5-6 h.
[0062] In the present invention, the first drying conditions can be selected in a wide range. Preferably, the first drying conditions include: a temperature of 50-200°C and a time of 0.5-8h.
[0063] In the present invention, the conditions for the first calcination can be selected in a wide range. Preferably, the conditions for the first calcination include: a temperature of 300-700°C and a time of 0.5-8h.
[0064] In a preferred embodiment, a solution containing a precursor of the modifying component is impregnated onto the molecular sieve by an impregnation method to perform metal modification, followed by a second drying and a second calcination.
[0065] In the present invention, there is no particular limitation on the type of the modified component precursor, and the VIB group metal element precursors conventionally defined in the art are applicable to the present invention. Preferably, the modified component precursor is selected from the soluble salts of each modified component; further preferably, the modified component precursor is selected from at least one of the ammonium salts, sulfates, nitrates, oxides and chlorides of each modified component; further preferably, the VIB group metal element precursor is selected from at least one of ammonium heptamolybdate, ammonium molybdate, ammonium phosphomolybdate, molybdenum trioxide, ammonium metatungstate and ethylammonium metatungstate.
[0066] In the present invention, the second drying conditions have a wide range of selection. Preferably, the second drying conditions include: temperature of 50-200°C, time of 0.5-8h; more preferably, the second drying conditions include: temperature of 60-150°C, time of 0.5-6h.
[0067] In the present invention, the second calcination conditions have a wide range of selection. Preferably, the second calcination conditions include: temperature of 300-700°C, time of 0.5-8h; more preferably, the second calcination conditions include: temperature of 350-650°C, time of 0.5-6h.
[0068] According to a specific embodiment of the present invention, the molecular sieve is subjected to at least one alkali modification, washing, ammonium exchange, first drying and first calcination, and then the modified component is introduced into the molecular sieve by an impregnation method for composite modification. Specifically, based on the dry weight of the original powder of the IMF type structure molecular sieve of ammonium or sodium type, the original powder of the molecular sieve is slurried with water according to the ratio of 1:5-1:20 of the dry basis to the water mass ratio, and stirred and mixed uniformly in a heated agitator at 60-120°C, and the alkaline solution is prepared according to the ratio of 10-40mL / g of the liquid-solid ratio of the solution to the original powder of the molecular sieve, and then the alkaline solution is added to the molecular sieve slurry, mixed uniformly, and continued to stir at 60-120°C for 0.5-8h, and washed, filtered, ammonium exchanged, and first dried. After the first calcination, it is prepared into an alkali-modified IMF type structure molecular sieve. Based on the dry weight of the alkali-modified IMF structure molecular sieve raw powder, a precursor solution containing a modified component is prepared in a ratio of 1:5 to 1:15 between the dry weight and the solution mass. The solution is then mixed evenly with the alkali-modified IMF structure molecular sieve raw powder, stirred and immersed in a heating stirrer at 60-120° C. for 2-8 hours, and then a second drying is performed followed by a second calcination to prepare a composite modified IMF structure molecular sieve.
[0069] In the present invention, the selection range of the mixing conditions of the modified component and the alkali-modified molecular sieve is relatively wide, preferably, the mixing temperature is 60-100°C and the time is 0.5-6h. In the present invention, the conventionally defined washing and filtering methods are applicable to the present invention, and the present invention will not be repeated.
[0070] In the present invention, the dry basis weight is the weight of the molecular sieve after calcination at 800° C. for 1 hour.
[0071] A second aspect of the present invention provides a method for preparing a hydrodesulfurization catalyst, wherein the method comprises:
[0072] (1) mixing an inorganic heat-resistant matrix and / or its precursor with a composite modified molecular sieve to form a mixture, and then performing a third drying and a third calcination to obtain a carrier;
[0073] (2) impregnating the support of step (1) with a solution containing an active component and an optional promoter precursor, and then performing a fourth drying and a fourth calcination to obtain a hydrodesulfurization catalyst;
[0074] The active component is selected from at least one of the metal elements of Group VIII and at least one of the metal elements of Group VIB; the auxiliary agent is selected from at least one of fluorine, phosphorus and boron;
[0075] Based on the total amount of the composite modified molecular sieve, the content of the modified component calculated as oxide is 1-20 wt %; based on the total amount of the composite modified molecular sieve, the total acid content of the composite modified molecular sieve is 0.85-1.5 mmol NH3·g -1 The mesoporous volume of the composite modified molecular sieve accounts for 20-80% of the total pore volume.
[0076] The preparation method of the invention is simple to operate, has a short process, and the prepared catalyst has good stability. It can give full play to the synergistic effect between the molecular sieve acid center and the active metal, promote the desulfurization reaction, and improve the desulfurization activity.
[0077] In a preferred embodiment, the inorganic heat-resistant matrix, the composite modified molecular sieve, the active component and the optional auxiliary agent are used in such an amount that, based on the total amount of the catalyst, the content of the inorganic heat-resistant matrix is 20-80% by weight, the content of the composite modified molecular sieve is 5-40% by weight, the content of the Group VIII metal calculated as oxide is 2-10% by weight, the content of the Group VIB metal calculated as oxide is 10-40% by weight, and the content of the auxiliary agent calculated as oxide is 0-80% by weight. %; further preferably, the inorganic heat-resistant matrix, the composite modified molecular sieve, the active component and the optional auxiliary agent are used in such an amount that, in the prepared catalyst, based on the total amount of catalyst, the content of the inorganic heat-resistant matrix is 30-70% by weight, the content of the composite modified molecular sieve is 5-30% by weight, the content of the Group VIII metal calculated as oxide is 2-8% by weight, the content of the Group VIB metal calculated as oxide is 10-30% by weight, and the content of the auxiliary agent calculated as oxide is 0-7% by weight.
[0078] In the present invention, the type of the inorganic heat-resistant matrix in step (1) has been described in the first aspect and will not be repeated here.
[0079] In the present invention, the precursor of the inorganic heat-resistant matrix is any substance that can be converted into an oxide matrix by subsequent calcination. Those skilled in the art can select the specific type of the inorganic heat-resistant matrix, and the present invention will not repeat it here. Preferably, the precursor of the alumina is selected from at least one of gibbsite, diaspore, diaspore, hard water stone, boehmite and pseudo-boehmite. This preferred embodiment can be used to prepare a suitable and adjustable specific surface area and pore distribution, and the preparation process can control different calcination temperatures to obtain different crystalline phases, and at the same time has a certain acidity, which is beneficial to improve the catalytic activity.
[0080] In the present invention, there is no specific limitation on the molding method in step (1). The molding methods conventionally defined in the art are applicable to the present invention, for example, tableting, ball rolling, extrusion and the like. Specifically, it can be obtained by the following method: the molding comprises mixing an inorganic heat-resistant matrix and / or its precursor with a composite modified molecular sieve, an optional auxiliary agent precursor and an extrusion aid and / or a sol agent, and then extruding and molding.
[0081] In the present invention, there is no specific limitation on the type and amount of the extrusion aid and the peptizing agent. Those skilled in the art can select the type and amount of the extrusion aid and the peptizing agent within a reasonable range according to the specific conditions of the extrusion molding. Preferably, the extrusion aid is selected from at least one of sesbania powder, dextrin and methylcellulose. Preferably, the peptizing agent is selected from at least one of nitric acid, acetic acid and citric acid.
[0082] In a preferred embodiment, based on the total amount of the catalyst, the amount of the extrusion aid is 0-6% by weight, and the amount of the peptizer is 0-5% by weight.
[0083] In the present invention, the third drying conditions in step (1) can be selected in a wide range. Preferably, in step (1), the third drying conditions include: a temperature of 100-200°C and a time of 2-12 hours; more preferably, a temperature of 100-150°C and a time of 2-8 hours.
[0084] In the present invention, the conditions for the third calcination in step (1) can be selected in a wide range. Preferably, in step (1), the conditions for the third calcination include: a temperature of 350-650°C and a time of 2-6 hours; more preferably, a temperature of 400-600°C and a time of 3-5 hours.
[0085] In the present invention, the composition and preparation method of the composite modified molecular sieve have been described in the first aspect and will not be repeated here.
[0086] In the present invention, there is no particular limitation on the diameter of the carrier. Preferably, the equivalent diameter of the carrier is 1-4 mm, more preferably 1.2-3.6 mm.
[0087] In the present invention, there is no particular limitation on the shape of the carrier. Preferably, the shape of the carrier is cylindrical, clover, four-leaf clover, butterfly or honeycomb.
[0088] In a preferred embodiment, in step (2), the active component is selected from at least one of iron, cobalt, nickel, ruthenium, rhodium, palladium, osmium, iridium and platinum and at least one of chromium, molybdenum and tungsten, more preferably molybdenum and / or tungsten and cobalt and / or nickel.
[0089] In the present invention, in step (2), the active component is introduced by an active component precursor, and the active component precursors conventionally defined in the art are applicable to the present invention. Preferably, the active component precursor is selected from the soluble salts of each active component, and further preferably, the active component precursor is selected from at least one of cobalt nitrate, basic cobalt carbonate, cobalt acetate, cobalt sulfate, nickel nitrate, basic nickel carbonate, nickel acetate and nickel sulfate, and at least one of ammonium heptamolybdate, ammonium molybdate, ammonium phosphomolybdate, molybdenum trioxide, ammonium metatungstate and ethylammonium metatungstate.
[0090] In the present invention, the active component can be introduced into the carrier by a method conventionally defined in the art, such as an impregnation method. Specifically, the present invention adopts the following method: a solution containing a metal element of Group VIII and a precursor of a metal element of Group VIB is contacted with the carrier, and then a fourth drying and a fourth calcination are performed. In the present invention, there is no specific limitation on the order of introduction of the metal element of Group VIII and the metal element of Group VIB. The precursors of the metal element of Group VIII and the metal element of Group VIB can be prepared into solutions and then contacted with the carrier, or the precursors of the metal element of Group VIII and the metal element of Group VIB can be prepared into a mixed solution and then mixed with the carrier, and then a fourth drying and a fourth calcination are performed. Preferably, the precursors of the metal element of Group VIII and the metal element of Group VIB are prepared into a mixed solution and then mixed with the carrier, and then a fourth drying and a fourth calcination are performed.
[0091] In the present invention, the fourth drying conditions can be selected in a wide range. Preferably, in step (2), the fourth drying conditions include: a temperature of 80-350°C and a time of 1-24 hours, and more preferably, a temperature of 100-250°C and a time of 2-12 hours.
[0092] In the present invention, the conditions for the fourth calcination are selected over a wide range. Preferably, in step (2), the conditions for the fourth calcination include: a temperature of 350-550°C and a time of 1-8 hours, and more preferably, a temperature of 400-500°C and a time of 2-7 hours. This preferred embodiment is conducive to the active component precursor being fully converted into the active component and being more evenly dispersed on the matrix, so that the catalyst has higher activity and stability.
[0093] In the present invention, there is no particular limitation on the method for introducing the auxiliary agent, and the auxiliary agent can be introduced by ion exchange, impregnation or coprecipitation, preferably by impregnation. Specifically, the present invention adopts the following method: in step (2), a solution containing an auxiliary agent precursor is mixed with a solution containing an active component precursor to prepare a mixed solution, and then the mixed solution is contacted with the support and then subjected to a fourth drying and a fourth calcination. The conditions for the fourth drying and the fourth calcination in the above step (2) have been described in the previous content and will not be repeated here.
[0094] In the present invention, there is no particular limitation on the type of the auxiliary agent precursor, and the conventionally defined precursors in the art are applicable to the present invention. Preferably, the precursor of phosphorus is selected from at least one of diammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid and hypophosphorous acid, the precursor of fluorine is selected from at least one of fluorosilicic acid, ammonium fluoride, ammonium fluorosilicate and ammonium fluoroborate, and the precursor of boron is selected from at least one of boric acid, borax, boron trifluoride and potassium pentaborate.
[0095] In the present invention, there is no specific limitation on the concentration of the precursor solution containing the auxiliary agent, and those skilled in the art can select it according to actual needs. Preferably, the solid content of the precursor solution containing the auxiliary agent is 20-70% by weight.
[0096] The third aspect of the present invention provides a use of the hydrodesulfurization catalyst described in the first aspect or the hydrodesulfurization catalyst prepared by the preparation method described in the second aspect in the hydrodesulfurization reaction of a raw material containing sterically hindered molecules.
[0097] In the present invention, preferably, the raw material containing sterically hindered molecules refers to a diesel raw material containing alkyl-substituted dibenzothiophene sulfur-containing compounds, preferably a dibenzothiophene compound with alkyl substituents at the 4- and 6-positions, further preferably 4-methyldibenzothiophene and / or 4,6-dimethyldibenzothiophene, further preferably 4,6-dimethyldibenzothiophene, and further preferably a n-decane raw material with a content of 0.33-0.66 weight %.
[0098] In a preferred embodiment, the hydrodesulfurization reaction conditions include: temperature of 200-500°C, pressure of 2-10 MPa, liquid hourly space velocity of 0.1-100 h -1 , the volume ratio of hydrogen to oil is 100-5000, more preferably the temperature is 200-400°C, the pressure is 3-8MPa, and the liquid hourly space velocity is 0.2-80h -1 , the volume ratio of hydrogen to oil is 200-1000.
[0099] In a preferred embodiment, the catalyst provided by the present invention needs to be sulfurized with sulfur, hydrogen sulfide or sulfur-containing raw materials in a hydrogen-containing atmosphere before use. In the present invention, there is no particular limitation on the sulfurization method, which can be dry sulfurization or wet sulfurization.
[0100] In the present invention, there is no particular limitation on the vulcanization conditions. Preferably, the vulcanization reaction temperature is 120-400°C, the reaction time is 0.5-10h, and the volume space velocity is 0.5-200h -1 , the hydrogen-oil volume ratio is 100-2000, and the hydrogen partial pressure is 0.1-10MPa.
[0101] In a preferred embodiment, the sulfidation treatment is performed by in-situ sulfidation in a sulfidation reactor or outside a sulfidation reactor.
[0102] The present invention will be described in detail below through examples. Unless otherwise specified, the reagents used in the present invention are all analytically pure reagents.
[0103] Examples 1-6 and Comparative Examples 1-5 are used to illustrate the preparation of the carrier
[0104] In the embodiment, the template X is a 1,5-bis(N-methylpyrrolidine)pentane bromide aqueous solution with a solid content of 58.9% by weight, produced by Guangzhou Dayou Fine Chemical Factory.
[0105] Example 1
[0106] An initial gel mixture containing solid silica gel (produced by Qingdao Ocean Chemical Co., Ltd., industrial pure, SiO2 content 92.2% by weight), sodium aluminate solution (produced by Changling Catalyst Plant, Al2O3 content 8.5% by weight, Na2O content 6.3% by weight), template X, deionized water and sodium hydroxide was uniformly mixed, and the molar ratio of the reactants was SiO2:Al2O3:X:H2O:NaOH=1:0.025:0.12:0.2:14; the prepared initial gel mixture was placed in a 40mL steel autoclave with a polytetrafluoroethylene liner and sealed with a cover, and then placed in a rotary oven (rotation speed of 20rpm) for crystallization, and reacted at 160°C for 7 days; the molecular sieve slurry after crystallization was subjected to ammonium exchange at 75°C for 4h, deionized water washing, filtration, 120°C drying for 5h and 550°C calcination for 6h to obtain the IM-5 molecular sieve.
[0107] 50 grams of the IM-5 molecular sieve sample prepared above was mixed with 750 mL of deionized water at 65°C for slurrying, 2 grams of potassium hydroxide was dissolved in 250 mL of deionized water to prepare an alkaline solution and divided into 6 equal parts, and 1 part was slowly added to the molecular sieve slurry while stirring every 0.17 hours, and continued to stir evenly for 1 hour after all the alkaline solution was added. After washing with deionized water, filtering, and ammonium exchange at 75°C for 4 hours, the alkaline-modified IM-5 molecular sieve sample was obtained by drying and calcining at 120°C and 550°C for 3 hours, respectively.
[0108] 1.23 g of ammonium heptamolybdate was dissolved in 400 mL of deionized water to prepare a modified impregnation solution, and the modified impregnation solution was uniformly mixed with 49 g of the alkali-modified IM-5 molecular sieve sample obtained above at 80° C. for 2 hours, and then the temperature was slowly raised from room temperature to 120° C. and dried for 3 hours, and then calcined at 550° C. for 3 hours to obtain a composite modified IM-5 molecular sieve sample (No. Z-1, sodium oxide content 0.1% by weight, dry basis 0.91). The structural properties of the composite modified IM-5 molecular sieve are shown in Table 1, and the content of the VIB group modified metal element is shown in Table 2.
[0109] Take 29.1 grams of the above-mentioned composite modified IM-5 molecular sieve, mix it with 214.3 grams of pseudo-boehmite powder (produced by Changling Catalyst Factory, trade name PB powder, dry basis 0.7), 4.5 grams of sesbania powder, and 161.2 mL of an aqueous solution containing 3.6 mL of analytically pure (purity 65-68 weight %) nitric acid, extrude it into a butterfly-shaped strip with an equivalent diameter of the circumscribed circle of 1.5 mm, dry it at 120°C for 4 hours, and calcine it at 580°C for 3 hours to prepare the carrier S-1.
[0110] Example 2
[0111] The IM-5 molecular sieve was synthesized in the same manner as in Example 1, and then subjected to alkali modification to obtain an alkali-modified IM-5 molecular sieve sample.
[0112] 4.91 g of ammonium heptamolybdate was dissolved in 400 mL of deionized water to prepare a modified impregnation solution. The modified impregnation solution was uniformly mixed with 46 g of the alkali-modified IM-5 molecular sieve sample obtained above at 80° C. for 2 hours, and then the temperature was slowly raised from room temperature to 120° C. and dried for 3 hours. Then, the mixture was calcined at 550° C. for 3 hours to obtain a composite modified IM-5 molecular sieve sample (No. Z-2, sodium oxide content 0.1 wt %, dry basis 0.91). The structural properties of the composite modified IM-5 molecular sieve are shown in Table 1, and the content of the VIB group modified metal element is shown in Table 2.
[0113] The carrier S-2 was prepared according to the method of Example 1.
[0114] Example 3
[0115] The IM-5 molecular sieve was synthesized and alkali-modified according to the same method as in Example 1, except that after the prepared IM-5 molecular sieve was subjected to an alkali-modification treatment, washed and dried, the molecular sieve sample was subjected to a second alkali-modification treatment in the same manner as the first alkali-modification to obtain an alkali-modified IM-5 molecular sieve sample.
[0116] 2.45 g of ammonium heptamolybdate was dissolved in 400 mL of deionized water to prepare a modified impregnation solution, and the modified impregnation solution was uniformly mixed with 48 g of the twice alkali-modified IM-5 molecular sieve sample obtained above at 80° C. for 2 hours, and then the temperature was slowly raised from room temperature to 120° C. and dried for 3 hours, and then calcined at 550° C. for 3 hours to obtain a composite modified IM-5 molecular sieve sample (No. Z-3, sodium oxide content 0.1 wt %, dry basis 0.91). The structural properties of the composite modified IM-5 molecular sieve are shown in Table 1, and the content of the VIB group modified metal element is shown in Table 2.
[0117] Take 29.2 grams of the above-mentioned composite modified IM-5 molecular sieve, mix it with 214.3 grams of pseudo-boehmite powder (produced by Changling Catalyst Factory, trade name PB powder, dry basis 0.7), 4.5 grams of sesbania powder, and 161.3 mL of an aqueous solution containing 3.6 mL of analytically pure (purity 65-68 weight %) nitric acid, extrude it into a butterfly-shaped strip with an equivalent diameter of the circumscribed circle of 1.5 mm, dry it at 120°C for 4 hours, and calcine it at 580°C for 3 hours to prepare the carrier S-3.
[0118] Example 4
[0119] The same method as in Example 1 was used to prepare ZSM-5 molecular sieve (produced by Changling Catalyst Factory, with a specific surface area of 378 m 2 / g, pore volume of 0.217mL / g, dry basis 0.92) was alkali-modified to obtain an alkali-modified ZSM-5 molecular sieve sample.
[0120] 2.45 g of ammonium heptamolybdate was dissolved in 400 mL of deionized water to prepare a modified impregnation solution. The modified impregnation solution was uniformly mixed with 48 g of the alkali-modified ZSM-5 molecular sieve sample obtained above at 80° C. for 2 hours, and then the temperature was slowly raised from room temperature to 120° C. and dried for 3 hours. Then, the mixture was calcined at 550° C. for 3 hours to obtain a composite modified ZSM-5 molecular sieve sample (No. Z-4, sodium oxide content 0.1 wt %, dry basis 0.92). The structural properties of the composite modified ZSM-5 molecular sieve are shown in Table 1, and the content of the VIB group modified metal element is shown in Table 2.
[0121] Take 28.7 grams of the above-mentioned composite modified ZSM-5 molecular sieve, mix it with 214.3 grams of pseudo-boehmite powder (produced by Changling Catalyst Factory, trade name PB powder, dry basis 0.7), 4.5 grams of sesbania powder, and 160.8 mL of an aqueous solution containing 3.6 mL of analytically pure (purity 65-68 weight %) nitric acid, extrude it into a butterfly-shaped strip with an equivalent diameter of the circumscribed circle of 1.5 mm, dry it at 120°C for 4 hours, and calcine it at 580°C for 3 hours to prepare the carrier S-4.
[0122] Example 5
[0123] The same method as in Example 1 was used to prepare a β molecular sieve (produced by Changling Catalyst Factory, with a specific surface area of 579 m 2 / g, pore volume of 0.527mL / g, dry basis 0.85) was alkali-modified to obtain an alkali-modified β molecular sieve sample.
[0124] 2.45 g of ammonium heptamolybdate was dissolved in 400 mL of deionized water to prepare a modified impregnation solution, and the modified impregnation solution was uniformly mixed with 48 g of the alkali-modified β molecular sieve sample obtained above at 80° C. for 2 hours, and then the temperature was slowly raised from room temperature to 120° C. and dried for 3 hours, and then calcined at 550° C. for 3 hours to obtain a composite modified β molecular sieve sample (No. Z-5, sodium oxide content 0.1 wt %, dry basis 0.85). The structural properties of the composite modified β molecular sieve are shown in Table 1, and the content of the VIB group modified metal element is shown in Table 2.
[0125] Take 31.0 grams of the above-mentioned composite modified β molecular sieve, mix it with 214.3 grams of pseudo-boehmite powder (produced by Changling Catalyst Factory, trade name PB powder, dry basis 0.7), 4.5 grams of sesbania powder, and 162.9 mL of an aqueous solution containing 3.6 mL of analytically pure (purity 65-68 weight %) nitric acid, extrude it into a butterfly-shaped strip with an equivalent diameter of the circumscribed circle of 1.5 mm, dry it at 120°C for 4 hours, and calcine it at 580°C for 3 hours to prepare the carrier S-5.
[0126] Example 6
[0127] The same method as in Example 1 was used to prepare MOR molecular sieve (produced by Changling Catalyst Factory, with a specific surface area of 429 m 2 / g, pore volume of 0.256mL / g, dry basis 0.91) was alkali-modified to obtain alkali-modified MOR molecular sieve.
[0128] 2.45 g of ammonium heptamolybdate was dissolved in 400 mL of deionized water to prepare a modified impregnation solution, and the modified impregnation solution was uniformly mixed with 48 g of the alkali-modified MOR molecular sieve sample obtained above at 80° C. for 2 hours, and then the temperature was slowly raised from room temperature to 120° C. and dried for 3 hours, and then calcined at 550° C. for 3 hours to obtain a composite modified MOR molecular sieve sample (No. Z-6, sodium oxide content 0.1 wt %, dry basis 0.91). The structural properties of the composite modified MOR molecular sieve are shown in Table 1, and the content of the VIB group modified metal element is shown in Table 2.
[0129] Take 29.2 grams of the above-mentioned composite modified MOR molecular sieve, mix it with 214.3 grams of pseudo-boehmite powder (produced by Changling Catalyst Factory, trade name PB powder, dry basis 0.7), 4.5 grams of sesbania powder, and 161.3 mL of an aqueous solution containing 3.6 mL of analytically pure (purity 65-68 weight %) nitric acid, extrude it into a butterfly-shaped strip with an equivalent diameter of the circumscribed circle of 1.5 mm, dry it at 120°C for 4 hours, and calcine it at 580°C for 3 hours to prepare the carrier S-6.
[0130] Comparative Example 1
[0131] 214.3 g of PB powder (dry basis 0.7) was mixed with 3.8 g of sesbania powder and 135.0 mL of an aqueous solution containing 3.0 mL of analytically pure (purity 65-68 wt%) nitric acid, and extruded into butterfly-shaped strips with an equivalent circumscribed circle diameter of 1.5 mm. The strips were dried at 120°C for 4 hours and calcined at 580°C for 3 hours to prepare the carrier SD-1.
[0132] Comparative Example 2
[0133] The IM-5 molecular sieve (No. ZD-2, sodium oxide content 0.1%, dry basis 0.92) was synthesized in the same manner as in Example 1 without modification. The structural properties of the molecular sieve are shown in Table 1.
[0134] Take 28.8 g of ZD-2 molecular sieve, mix it with 214.3 g of PB powder (dry basis 0.7), 4.5 g of sesbania powder, and 160.9 mL of an aqueous solution containing 3.6 mL of analytically pure (purity 65-68 wt%) nitric acid, squeeze it into a butterfly-shaped strip with an equivalent diameter of the circumscribed circle of 1.5 mm, dry it at 120°C for 4 hours, and calcine it at 580°C for 3 hours to prepare the carrier SD-2.
[0135] Comparative Example 3
[0136] The IM-5 molecular sieve was synthesized and alkali-modified (No. ZD-3, sodium oxide content 0.1 wt%, dry basis 0.91) according to the same method as in Example 1, without modification with a Group VIB metal. The structural properties of the modified molecular sieve are shown in Table 1.
[0137] Take 29.0 grams of ZD-3 molecular sieve, mix it with 214.3 grams of pseudo-boehmite powder (produced by Changling Catalyst Factory, trade name PB powder, dry basis 0.7), 4.5 grams of sesbania powder, and 161.1 mL of an aqueous solution containing 3.6 mL of analytically pure (purity 65-68 weight%) nitric acid, extrude it into a butterfly-shaped strip with an equivalent diameter of the circumscribed circle of 1.5 mm, dry it at 120°C for 4 hours, and calcine it at 580°C for 3 hours to prepare a carrier SD-3.
[0138] Comparative Example 4
[0139] According to the method of Example 1, IM-5 molecular sieve was synthesized and subjected to Group VIB metal modification treatment (No. ZD-4, sodium oxide content 0.1 wt%, dry basis 0.92), without alkali modification treatment. The structural properties of the modified molecular sieve are shown in Table 1, and the content of the Group VIB modified metal element is shown in Table 2.
[0140] Take 28.8 grams of ZD-5 molecular sieve, mix it with 214.3 grams of pseudo-boehmite powder (produced by Changling Catalyst Factory, trade name PB powder, dry basis 0.7), 4.5 grams of sesbania powder, and 161.0 mL of an aqueous solution containing 3.6 mL of analytically pure (purity 65-68 weight %) nitric acid, extrude it into a butterfly-shaped strip with an equivalent diameter of the circumscribed circle of 1.5 mm, dry it at 120°C for 4 hours, and calcine it at 580°C for 3 hours to prepare a carrier SD-4.
[0141] Table 1
[0142]
[0143]
[0144] Note: In Table 1, in Examples 1-6, the total acid amount is based on the total amount of the composite modified molecular sieve; in Comparative Example 2, the total acid amount is based on the total amount of the molecular sieve; in Comparative Examples 3-4, the total acid amount is based on the total amount of the modified molecular sieve.
[0145] As shown in Table 1, after the composite modification of IM-5, its silicon-aluminum atomic ratio is slightly reduced, while the specific surface area increases or remains stable, the pore volume increases significantly, and the proportion of mesopore volume increases, indicating that after the composite modification, the pore structure of the molecular sieve is richer, more secondary pores (mesopores) are generated, and the skeleton structure remains basically stable. After the composite modification, the total acid content of the IM-5 molecular sieve increases, which helps more acid centers participate in the reaction and promotes the conversion of sulfur-containing compounds.
[0146] Table 2
[0147]
[0148]
[0149] Note: In Table 2, in Examples 1-6, the content of each substance is based on the total amount of the composite modified molecular sieve; in Comparative Example 2, the content of each substance is based on the total amount of the molecular sieve; in Comparative Examples 3-4, the content of each substance is based on the total amount of the modified molecular sieve.
[0150] Examples 7-12 and Comparative Examples 5-8 are used to illustrate the preparation of catalysts
[0151] Example 7
[0152] 100 g of S-1 carrier was impregnated with 70 mL of aqueous solution containing 36.5 g of molybdenum trioxide (product of Aladdin Reagent (Shanghai) Co., Ltd.), 5.2 g of basic cobalt carbonate (product of Sinopharm Chemical Reagent Co., Ltd.) calculated as cobalt oxide, and 9.1 g of phosphoric acid (product of Beijing Chemical Plant, phosphoric acid content 85 wt%), dried at 120° C. for 4 hours, and calcined at 400° C. for 3 hours to obtain catalyst C-1. The contents of each substance in the catalyst are shown in Table 3.
[0153] Example 8
[0154] 100 g of the S-2 carrier was impregnated with 70 mL of an aqueous solution containing 35.3 g of molybdenum trioxide (a product of Aladdin Reagent (Shanghai) Co., Ltd.), 5.1 g of basic cobalt carbonate (a product of Sinopharm Chemical Reagent Co., Ltd.) calculated as cobalt oxide, and 9.0 g of phosphoric acid (a product of Beijing Chemical Plant, with a phosphoric acid content of 85 wt%), dried at 120° C. for 4 hours, and calcined at 400° C. for 3 hours to obtain catalyst C-2. The contents of each substance in the catalyst are shown in Table 3.
[0155] Example 9
[0156] 100 g of S-3 carrier was impregnated with 70 mL of aqueous solution containing 36.1 g of molybdenum trioxide (product of Aladdin Reagent (Shanghai) Co., Ltd.), 5.1 g of basic cobalt carbonate (product of Sinopharm Chemical Reagent Co., Ltd.) calculated as cobalt oxide, and 9.1 g of phosphoric acid (product of Beijing Chemical Plant, phosphoric acid content 85 wt%), dried at 120° C. for 4 hours, and calcined at 400° C. for 3 hours to obtain catalyst C-3. The contents of various substances in the catalyst are shown in Table 3.
[0157] Example 10
[0158] 100 g of the S-4 carrier was impregnated with 70 mL of an aqueous solution containing 36.1 g of molybdenum trioxide (a product of Aladdin Reagent (Shanghai) Co., Ltd.), 5.1 g of basic cobalt carbonate (a product of Sinopharm Chemical Reagent Co., Ltd.) calculated as cobalt oxide, and 9.1 g of phosphoric acid (a product of Beijing Chemical Plant, with a phosphoric acid content of 85 wt%), dried at 120° C. for 4 hours, and calcined at 400° C. for 3 hours to obtain a catalyst C-4. The contents of the various substances in the catalyst are shown in Table 3.
[0159] Embodiment 11
[0160] 100 g of S-5 carrier was impregnated with 70 mL of aqueous solution containing 36.1 g of molybdenum trioxide (product of Aladdin Reagent (Shanghai) Co., Ltd.), 5.1 g of basic cobalt carbonate (product of Sinopharm Chemical Reagent Co., Ltd.) calculated as cobalt oxide, and 9.1 g of phosphoric acid (product of Beijing Chemical Plant, phosphoric acid content 85 wt%), dried at 120° C. for 4 hours, and calcined at 400° C. for 3 hours to obtain catalyst C-5. The contents of various substances in the catalyst are shown in Table 3.
[0161] Example 12
[0162] 100 g of S-6 carrier was impregnated with 70 mL of aqueous solution containing 36.1 g of molybdenum trioxide (product of Aladdin Reagent (Shanghai) Co., Ltd.), 5.1 g of basic cobalt carbonate (product of Sinopharm Chemical Reagent Co., Ltd.) calculated as cobalt oxide, and 9.1 g of phosphoric acid (product of Beijing Chemical Plant, phosphoric acid content 85 wt%), dried at 120° C. for 4 hours, and calcined at 400° C. for 3 hours to obtain catalyst C-6. The contents of various substances in the catalyst are shown in Table 3.
[0163] Comparative Example 5
[0164] 100 g of SD-1 carrier was impregnated with 70 mL of aqueous solution containing 36.9 g of molybdenum trioxide (product of Aladdin Reagent (Shanghai) Co., Ltd.), 5.2 g of basic cobalt carbonate (product of Sinopharm Chemical Reagent Co., Ltd.) calculated as cobalt oxide, and 9.1 g of phosphoric acid (product of Beijing Chemical Plant, phosphoric acid content 85 wt%), dried at 120° C. for 4 hours, and calcined at 400° C. for 3 hours to obtain catalyst D-1. The contents of each substance in the catalyst are shown in Table 3.
[0165] Comparative Example 6
[0166] 100 g of SD-2 carrier was impregnated with 70 mL of aqueous solution containing 36.9 g of molybdenum trioxide (product of Aladdin Reagent (Shanghai) Co., Ltd.), 5.2 g of basic cobalt carbonate (product of Sinopharm Chemical Reagent Co., Ltd.) calculated as cobalt oxide, and 9.1 g of phosphoric acid (product of Beijing Chemical Plant, phosphoric acid content 85 wt%), dried at 120° C. for 4 hours, and calcined at 400° C. for 3 hours to obtain catalyst D-2. The contents of each substance in the catalyst are shown in Table 3.
[0167] Comparative Example 7
[0168] 100 g of SD-3 carrier was impregnated with 70 mL of aqueous solution containing 36.9 g of molybdenum trioxide (product of Aladdin Reagent (Shanghai) Co., Ltd.), 5.2 g of basic cobalt carbonate (product of Sinopharm Chemical Reagent Co., Ltd.) calculated as cobalt oxide, and 9.1 g of phosphoric acid (product of Beijing Chemical Plant, phosphoric acid content 85 wt%), dried at 120° C. for 4 hours, and calcined at 400° C. for 3 hours to obtain catalyst D-3. The contents of each substance in the catalyst are shown in Table 3.
[0169] Comparative Example 8
[0170] 100 g of SD-4 carrier was impregnated with 70 mL of aqueous solution containing 36.5 g of molybdenum trioxide (product of Aladdin Reagent (Shanghai) Co., Ltd.), 5.2 g of basic cobalt carbonate (product of Sinopharm Chemical Reagent Co., Ltd.) calculated as cobalt oxide, and 9.1 g of phosphoric acid (product of Beijing Chemical Plant, phosphoric acid content 85 wt%), dried at 120° C. for 4 hours, and calcined at 400° C. for 3 hours to obtain catalyst D-4. The contents of each substance in the catalyst are shown in Table 3.
[0171] Table 3
[0172]
[0173] Performance Testing
[0174] The catalysts of the above-mentioned Examples 7-12 and Comparative Examples 5-8 were crushed into particles of 0.25-0.38 mm, 0.15 g of the catalyst sample was weighed and mixed with 1 g of quartz sand of the same particle size and then loaded into a fixed bed reactor. The catalyst was pre-sulfided before the reaction, and the sulfiding conditions were: cyclohexane solution with a mass fraction of CS2 of 5% as sulfiding oil, hydrogen partial pressure of 4.0 MPa, temperature of 360°C, sulfiding time of 4 hours, and hydrogen-oil volume ratio of 900.
[0175] After the presulfurization is completed, the reaction oil is switched to a 0.45 wt% n-decane solution of 4,6-DMDBT. The reaction conditions are: hydrogen partial pressure of 4.0 MPa, reaction temperature of 300°C, reaction oil flow rate of 0.2 mL / min, hydrogen-oil volume ratio of 500, and sampling and analysis are performed after stabilization for 2 hours.
[0176] The conversion rate of 4,6-DMDBT, the selectivity of the direct desulfurization pathway, the desulfurization rate, the total activity of the desulfurization reaction, the direct desulfurization activity and the reaction hydrogen consumption were calculated using the following formulas. The results are shown in Table 4.
[0177] If the direct desulfurization activity of the catalyst prepared in Comparative Example 5 is defined as 100, the direct desulfurization relative activities of the catalysts in other test examples can be calculated, and the results are shown in Table 4.
[0178]
[0179]
[0180]
[0181]
[0182] Direct desulfurization activity = total desulfurization reaction activity × selectivity of direct desulfurization pathway
[0183]
[0184] Table 4
[0185]
[0186]
[0187] As shown in the above table, the conversion rate and desulfurization rate of the composite modified molecular sieve catalyst in the embodiment are higher than those of the catalyst D-1 without molecular sieve, and the direct desulfurization path selectivity of the catalyst is relatively high, and the direct desulfurization activity is also significantly improved. Under the same premise of molecular sieve, compared with the catalyst D-2 containing unmodified molecular sieve catalyst, the catalyst D-3 containing only alkali-modified molecular sieve, and the catalyst D-4 containing only VIB group metal modified molecular sieve, the conversion rate, desulfurization rate, direct desulfurization path selectivity and direct desulfurization activity of the corresponding catalyst after composite modification of molecular sieve are significantly improved. From the result of reaction hydrogen consumption, by adding composite modified molecular sieve, the desulfurization reaction hydrogen consumption of the catalyst is significantly reduced, and the utilization efficiency of hydrogen in the desulfurization reaction process is improved. The above data all show that the catalyst containing composite modified molecular sieve provided by the present invention has a good application prospect in the ultra-deep hydrodesulfurization process of diesel.
[0188] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A hydrodesulfurization catalyst, It is characterized in that The catalyst comprises a carrier, an active component loaded on the carrier and an optional auxiliary agent, wherein the carrier comprises an inorganic heat-resistant matrix and a composite modified molecular sieve, wherein the composite modified molecular sieve comprises a molecular sieve and a modified component, wherein the modified component is selected from at least one of the metals of Group VIB; based on the total amount of the composite modified molecular sieve, the content of the modified component in terms of oxide is 1-20 wt %; based on the total amount of the composite modified molecular sieve, the total acid content of the composite modified molecular sieve is 0.85-1.5 mmol NH 3 ·g -1 The proportion of the mesopore volume of the composite modified molecular sieve to the total pore volume is 20-80%; the active component includes at least one of the metals of Group VIII and at least one of the metals of Group VIB, and the auxiliary agent is selected from at least one of fluorine, phosphorus and boron.
2. The hydrodesulfurization catalyst according to claim 1, in, Based on the total amount of the catalyst, the content of the inorganic heat-resistant matrix is 20-80% by weight, the content of the composite modified molecular sieve is 5-40% by weight, the content of the Group VIII metal calculated as oxide is 2-10% by weight, the content of the Group VIB metal calculated as oxide is 10-40% by weight, and the content of the additive calculated as oxide is 0-8% by weight; Preferably, based on the total amount of the catalyst, the content of the inorganic heat-resistant matrix is 30-70% by weight, the content of the composite modified molecular sieve is 5-30% by weight, the content of the Group VIII metal calculated as oxide is 2-8% by weight, the content of the Group VIB metal calculated as oxide is 10-30% by weight, and the content of the additive calculated as oxide is 0-7% by weight.
3. The hydrodesulfurization catalyst according to claim 1 or 2, in, The inorganic heat-resistant matrix is selected from at least one of aluminum oxide, silicon oxide, titanium oxide, magnesium oxide, aluminum oxide-magnesium oxide, silicon oxide-aluminum oxide, silicon oxide-magnesium oxide, silicon oxide-zirconium oxide, silicon oxide-thoria, silicon oxide-beryllium oxide, silicon oxide-titania, silicon oxide-aluminum oxide-thoria, silicon oxide-aluminum oxide-titania, silicon oxide-aluminum oxide-magnesium oxide, silicon oxide-aluminum oxide-zirconium oxide, phosphorus oxide-aluminum oxide, phosphorus oxide-silicon oxide-aluminum oxide, and natural zeolite, preferably aluminum oxide; And / or, the active component is selected from at least one of iron, cobalt, nickel, ruthenium, rhodium, palladium, osmium, iridium and platinum and at least one of chromium, molybdenum and tungsten, preferably molybdenum and / or tungsten and cobalt and / or nickel.
4. The hydrodesulfurization catalyst according to claim 1 or 2, in, Based on the total amount of the composite modified molecular sieve, the content of the modified component calculated as oxide is 1-10% by weight; And / or, based on the total amount of the composite modified molecular sieve, the total acid amount of the composite modified molecular sieve is 0.85-1mmolNH 3 ·g -1 ; And / or, the proportion of the mesopore volume of the composite modified molecular sieve to the total pore volume is 25-75%, preferably 50-70%.
5. The hydrodesulfurization catalyst according to claim 1 or 2, in, The modifying component is selected from at least one of chromium, molybdenum and tungsten, preferably molybdenum and / or tungsten; Preferably, based on the total amount of the composite modified molecular sieve, the content of the molecular sieve is 80-99% by weight, the content of molybdenum oxide is 1-10% by weight, and the content of tungsten oxide is 0-10% by weight; further preferably, based on the total amount of the composite modified molecular sieve, the content of the molecular sieve is 82-99% by weight, the content of molybdenum oxide is 1-9% by weight, and the content of tungsten oxide is 0-9% by weight; And / or, the molecular sieve is at least one selected from the group consisting of IMF type molecular sieve, MFI type molecular sieve, Beta type molecular sieve, MOR type molecular sieve and FAU type molecular sieve, preferably IMF type molecular sieve.
6. The hydrodesulfurization catalyst according to claim 1 or 2, in, The preparation method of the composite modified molecule comprises: contacting the molecular sieve with a base to perform at least one base modification, performing a first drying and a first calcination in sequence after ammonium exchange, and then introducing the modified component into the molecular sieve to perform metal modification.
7. The hydrodesulfurization catalyst according to claim 6, in, The base is selected from at least one of sodium hydroxide, potassium hydroxide, ammonium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate and potassium bicarbonate, preferably sodium hydroxide and / or potassium hydroxide; and / or, the concentration of the base is 0.001-0.5 mol / L, preferably 0.05-0.1 mol / L; and / or, the liquid-to-solid ratio of the mixed solution during the alkali modification is 10-40 mL / g, preferably 15-30 mL / g; And / or, the conditions for the alkali modification include: temperature of 60-120°C, time of 0.5-8h; preferably, the conditions for the alkali modification include: temperature of 60-100°C, time of 0.5-6h; And / or, the number of base modification is 1-3 times; And / or, the conditions of the ammonium exchange include: temperature of 60-100° C., time of 0.5-6 h; And / or, the first calcination conditions include: temperature of 300-700° C. and time of 0.5-8 h.
8. The hydrodesulfurization catalyst according to claim 6, in, Introducing a solution containing a precursor of a modification component into the molecular sieve for metal modification by at least one of an impregnation method, an ion exchange method, and a precipitation method, and then performing a second drying and a second calcination; Preferably, the modified component precursor is selected from at least one of the ammonium salt, sulfate, nitrate, oxide and chloride of each modified component; Preferably, the second calcination conditions include: temperature of 300-700° C. and time of 0.5-8 h.
9. A method for preparing a hydrodesulfurization catalyst, in, The method includes: (1) mixing an inorganic heat-resistant matrix and / or its precursor with a composite modified molecular sieve to form a mixture, and then performing a third drying and a third calcination to obtain a carrier; (2) impregnating the support of step (1) with a solution containing an active component and an optional promoter precursor, and then performing a fourth drying and a fourth calcination to obtain a hydrodesulfurization catalyst; The active component is selected from at least one of the metal elements of Group VIII and at least one of the metal elements of Group VIB; the auxiliary agent is selected from at least one of fluorine, phosphorus and boron; Based on the total amount of the composite modified molecular sieve, the content of the modified component calculated as oxide is 1-20 wt %; based on the total amount of the composite modified molecular sieve, the total acid content of the composite modified molecular sieve is 0.85-1.5 mmol NH 3 ·g -1 The mesoporous volume of the composite modified molecular sieve accounts for 20-80% of the total pore volume.
10. The preparation method according to claim 9, in, The inorganic heat-resistant matrix, the composite modified molecular sieve, the active component and the optional auxiliary agent are used in such an amount that, based on the total amount of the catalyst, the content of the inorganic heat-resistant matrix is 20-80% by weight, the content of the composite modified molecular sieve is 5-40% by weight, the content of the Group VIII metal calculated as oxide is 2-10% by weight, the content of the Group VIB metal calculated as oxide is 10-40% by weight, and the content of the auxiliary agent calculated as oxide is 0-8% by weight; Preferably, the inorganic heat-resistant matrix, composite modified molecular sieve, active component and optional auxiliary agent are used in such an amount that, based on the total amount of catalyst, the content of the inorganic heat-resistant matrix in the prepared catalyst is 30-70% by weight, the content of the composite modified molecular sieve is 5-30% by weight, the content of the Group VIII metal calculated as oxide is 2-8% by weight, the content of the Group VIB metal calculated as oxide is 10-30% by weight, and the content of the auxiliary agent calculated as oxide is 0-7% by weight.
11. The preparation method according to claim 9 or 10, in, In step (1), the inorganic heat-resistant matrix is selected from at least one of aluminum oxide, silicon oxide, titanium oxide, magnesium oxide, aluminum oxide-magnesium oxide, silicon oxide-aluminum oxide, silicon oxide-magnesium oxide, silicon oxide-zirconium oxide, silicon oxide-thorium oxide, silicon oxide-beryllium oxide, silicon oxide-titania, silicon oxide-aluminum oxide-thorium oxide, silicon oxide-aluminum oxide-titania, silicon oxide-aluminum oxide-magnesium oxide, silicon oxide-aluminum oxide-zirconium oxide, phosphorus oxide-aluminum oxide, phosphorus oxide-silicon oxide-aluminum oxide, and natural zeolite, preferably aluminum oxide; Preferably, the precursor of aluminum oxide is selected from at least one of gibbsite, diaspore, diaspore, diaspore, boehmite and pseudo-boehmite; And / or, in step (1), the conditions of the third calcination include: temperature of 350-650°C, time of 2-6h; preferably, temperature of 400-600°C, time of 3-5h.
12. The method according to claim 9 or 10, in, In step (1), the composite modified molecular sieve comprises a molecular sieve and a modifying component, and the modifying component is selected from at least one of the VIB Group metals; Preferably, the molecular sieve is at least one selected from the group consisting of IMF type molecular sieve, MFI type molecular sieve, Beta type molecular sieve, MOR type molecular sieve and FAU type molecular sieve; Preferably, the preparation method of the composite modified molecule comprises: contacting the molecular sieve with a base for at least one base modification, ammonium exchange, sequentially performing a first drying and a first calcination, and then introducing the modified component into the molecular sieve for metal modification; Preferably, a solution containing a precursor of the modifying component is introduced into the molecular sieve for metal modification by at least one of an impregnation method, an ion exchange method and a precipitation method, and then a second drying and a second calcination are performed; Preferably, the modifying component precursor is selected from at least one of the ammonium salt, sulfate, nitrate, oxide and chloride of each modifying component.
13. The method according to claim 9 or 10, in, In step (2), the active component is selected from at least one of iron, cobalt, nickel, ruthenium, rhodium, palladium, osmium, iridium and platinum and at least one of chromium, molybdenum and tungsten, preferably molybdenum and / or tungsten and cobalt and / or nickel; And / or, in step (2), the conditions of the fourth calcination include: temperature of 350-550° C., time of 1-8 h, preferably, temperature of 400-500° C., time of 2-7 h.
14. Use of the hydrodesulfurization catalyst according to any one of claims 1 to 8 or the hydrodesulfurization catalyst prepared by the preparation method according to any one of claims 9 to 13 in the hydrodesulfurization reaction of a raw material containing sterically hindered molecules.
Citation Information
Patent Citations
Method for synthesizing IM-5 molecular sieve
CN102452666A
Mesoporous ZSM-5 zeolite, mesoporous ZSM-5 zeolite-loaded metal sulfide catalyst and application
CN103787368A
Carrier of hydrogen desulfurization catalyst and preparation method and catalyst prepared by preparation method
CN105772109A
Synthesis of porous ZSM-5 zeolite and gamma-Al2O3 composite material and preparation of hydrodesulfurization catalyst
CN106391097A
Modified IM-5 molecular sieve and preparation method and application thereof
CN106391100A
Cited By
Preparation, application, regeneration and recovery method of Ni-doped defect WS2 catalyst
CN119793491A
Preparation, application, regeneration and recovery method of Ni-doped defective WS2 catalyst
CN119793491B
